FOREIGN EXPERIENCE IN IMPLEMENTING DIGITAL EDUCATION IN THE CONTEXT OF DIGITAL ECONOMY TRANSFORMATION - Valentyna Voronkova; Vitalina Nikitenko; Gennadiy Vasyl'chuk (Baltic Journal of Economic Studies, 2023)
The relevance of the research topic is that the study of foreign experiences in the implementation of digital education in the context of digital economic transformation is of great importance. In the context of digitalisation, developed countries are implementing digitalisation policies to promote the digital transformation of education, focusing on improving digital literacy and digital competence. The purpose of the study is to conceptualise the foreign experience of implementing digital education in the context of digital economy transformation. This study aims to examine the global implementation of digital education as a social and economic phenomenon. This study focuses on exploring the impact of the digital economy on the transformation of digital education. The research will focus on: (1) reflections on the concepts of digitalisation of education in advanced countries such as the USA, Japan, India, South Korea, Australia, the UK, Germany and China; (2) definition of connotations and attributes of the digital economy; (3) identification of smart education as a condition for the transformation of the digital economy. According to the study, advanced countries are adopting smart education concepts as a crucial step towards digitalising education to achieve a balance in developing high-quality education, enhancing its quality, expanding opportunities, and promoting the formation of lifelong digital competenciesIt is concluded that the promotion of higher education as a "smart digital transformation reform" contributes to the creation of a new educational environment in the digital age, providing convenient channels for obtaining digital resources. Informatisation of education as a factor of digital transformation has created new opportunities, provided students with intelligent data for learning, given a new impetus to education reform, facilitated large-scale individualised learning, and formed innovative concepts for implementing smart education as an extension of the capabilities of digital technologies and the impact of the digital economy on the transformation of digital education.